Intestinal atresias and intestinal failure in patients with TTC7A mutations - Katherine Culbreath, MD; Gregory Keefe, MD; Emily Nes, MD; Jamie Knell, MD; Sam M. Han, MD; Priyanka Chugh, MD; Grace Y. Han, BS; Alexandra N. Carey, MD; Lissette Jimenez, MD MPH; Jay R. Thiagarajah, MD PhD; Sung-Yun Pai, MD; Biren P. Modi, MD MPH; et al. (Journal of Pediatric Surgery Case Reports, 2022)
Mutations in the tetratricopeptide repeat domain 7A (TTC7A) gene are associated with severe intestinal disorders and combined immunodeficiency (CID), with poor long-term survival. This study describes the characteristics and clinical course of six patients with intestinal failure who were found to have biallelic TTC7A mutations, highlighting key management strategies for identifying these patients and improving their survival. Of the six patients included, five had multiple intestinal atresias (83%) and one had congenital enteropathy (17%). Pyloric web or atresia was present in 100% of patients. All patients had low CD3+ T-cell counts on flow cytometry, consistent with CID. Immunologic management consisted of intravenous immunoglobulin and antibiotic prophylaxis, while two patients (33%) underwent stem cell transplantation. All patients were initially dependent on parenteral nutrition, but two (33%) achieved enteral autonomy after undergoing intestinal transplantation. Patients were followed for a median of 7 years (IQR 4.75–9.25), with a long-term survival rate of 67%. The high incidence of pyloric atresia in this case series suggests that the presence of pyloric atresia, especially in the setting of other intestinal disorders, should prompt screening for CID and a genetic evaluation. Recognition of the mutation and involvement of appropriate interdisciplinary care teams are essential for optimizing survival of these complex patients.